Cardioprotective Potential of Garlic Oil and Its Active Constituent, Diallyl Disulphide, in Presence of Carvedilol during Chronic Isoprenaline Injection-Mediated Myocardial Necrosis in Rats - Syed Mohammed Basheeruddin Asdaq; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani (Molecules, 2021)
In isoprenaline (ISO)-induced myocardial infarcted rats, garlic oil (GO) and its main ingredient, diallyl disulfide (DADS), were examined for cardioprotective effects when used with carvedilol (CAR). GO, DADS and CAR were given to rats in their respective groups, either alone or together, with the addition of isoprenaline (3 mg/kg/day, subcutaneously) during the last 10 days of treatment. At the end of 14 days of treatment, blood samples were collected, the hearts were excised under anesthesia and weighed. Heart tissue homogenate was used to measure superoxide dismutase (SOD), catalase (CAT), and thiobarbituric acid reactive substances (TBARS). Furthermore, the serum activities of cardiac markers, including lactate dehydrogenase, creatine kinase, and cardiac troponin, were checked. Moreover, inflammatory markers including tumor necrosis factor alpha, interleukin one beta, interleukin six, and kappa bp65 subunit were assessed. Rats that received GO, DADS, and CAR exhibited a significant increase in the cardiac antioxidant enzyme activities with a simultaneous decrease in serum cardiac markers enzymes and inflammatory markers. The TBARS were significantly reduced in rats that received treatment. The addition of carvedilol to GO or DADS significantly elevated antioxidant activities and decreased the release of cardiac enzymes into blood circulation. Both DADS and GOl were almost similar in efficacy, indicating the potential role of DADS in garlic oil-mediated cardioprotection. Combining GO or DADS with CAR increased CAR’s cardioprotective impact and protected rats from developing ISO-induced myocardial infarction.